Proceedings of GeoShanghai 2018 International Conference: Transportation Geotechnics and Pavement Engineering (Springer Singapore, 2018)
This book is the fourth volume of the proceedings of the 4th GeoShanghai International Conference that was held on May 27 - 30, 2018. This volume, entitled "Transportation Geotechnics and Pavement Engineering", represents the recent advances and technologies in transportation geotechnics and pavement engineering. This book covers a wide range of topics, from transportation geotechnics, to geomechanics at various length scales, to pavement materials and structures. The book offers a unique mix of numerical modeling studies, experimental studies, and case studies from industry. It may be of interest to researchers and practitioners in the fields of transportation engineering and pavement engineering.